Use of Pyrogallol Red and Pyranine as Probes to Evaluate Antioxidant Capacities Towards Hypochlorite - Lissi-Gervaso, E; Aspee-Lamas, A (2013)
Hypochlorite is a strong oxidant able to induce deleterious effects in biological systems. The goal of this work was to investigate the use of PGR and PYR as probes in assays aimed at evaluating antioxidant activities towards hypochorite and apply it to plant extracts employed in Chilean folk medicine. The consumption of PGR and PYR was evaluated from the decrease in the visible absorbance and fluorescence intensity, respectively. Total phenolic content was determined by the Folin Ciocalteau assay. PGR and PYR react with hypochlorite with different kinetics, being considerably faster the consumption of PGR. Different stoichiometric values were also determined: 0.7 molecules of PGR and 0.33 molecules of PYR were bleached per each molecule of added hypochlorite. Both probes were protected by antioxidants, but the rate of PGR bleaching was too fast to perform a kinetic analysis. For PYR, the protection took place without changes in its initial consumption rate, suggesting a competition between the dye and the antioxidant for hypochlorite. Plant extracts protected PYR giving a PYR-HOCl index that follows the order: Fuchsia magellanica = Marrubium vulgare = Tagetes minuta > Chenopodium ambrosoides = Satureja montana > Thymus praecox. Based on both the kinetic data and the protection afforded by pure antioxidants, we selected PYR as the best probe. The proposed methodology allows evaluating an antioxidant capacity index of plant extracts related to the reactivity of the samples towards hypochlorite. © 2013 by the authors.